Polarization of terahertz radiation driven by incommensurate two-color laser pulses. Issue 19 (January 2020) - Li, Y N; Wang, G L; Zhang, L; Jiao, Z H; Zhao, S F; Zhou, X X
Synopsis: We investigate the polarization characteristics of terahertz (THz) emission from gaseous plasma induced by the two-color incommensurate femtosecond laser fields, which contains a circularly polarized laser field and a linear pulse. Our simulations show that strong linearly, elliptically, and circularly polarized THz radiation can be generated, by choosing appropriate wavelength, carrier-envelope phase and intensity for linear pump pulse.